An alternative clean-up column for the determination of polychlorinated biphenyls in solid matrices - Ndunda, Elizabeth N; Madadib, Vincent O; Mizaikoﬀ, Boris (Royal Society of Chemistry, 2016)
The need for continuous monitoring of polychlorinated biphenyls (PCBs) has necessitated the development of analytical techniques that are sensitive and selective with minimal reagent requirement.In light of this,we developed a column for clean-up of soil and sediment extracts, which is less demanding in terms of the amount of solvent and sorbent. The dual-layer column consists of acidiﬁed silica gel and molecularly imprinted polymers (MIPs). MIPs were synthesized via aqueous suspension polymerization using PCB 15 as the dummy template, 4-vinylpyridine as the functional monomer and ethylene glycol dimethacrylate as the cross-linker and the obtained particles characterized via SEM, BET, and batch rebinding assays. Pre-concentration of the spiked real-world water sample using MISPE gave recoveries between 85.2 and 104.4% (RSD < 8.69). On the other hand, the speciﬁc dual-layer column designed for clean-up of extracts from complex matrices provided recoveries of 91.6–102.5% (RSD < 4%) for spiked soil, which was comparable to clean-up using acidiﬁed silica (70.4–90.5%; RSD < 3.72%) and sulfoxide modiﬁed silica (89.7–103.0%; RSD < 13.0%). However, the polymers were reusable maintaining recoveries of 79.8– 111.8% after 30 cycles of regeneration and re-use, thereby availing a cost-eﬀective clean-up procedure for continuous monitoring of PCBs. Method detection limits were 0.01–0.08 ng g!1 and 0.002–0.01 ng mL!1 for solid matrices and water, respectively